Dwarf Elephant Grass (Pennisetum purpureum cv. Mott) as Forage for Ruminant - Juniar Sirait (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2017)
Availability of good quality forage is limited during dry season. Dwarf elephant grass is one of alternatives in providing high productivity and quality of forage. This paper aims to inform morphologhy characteristics, feed quality, and post harvest of dwarf elephant grass. Dwarf elephant grass (Pennisetum purpureum cv. Mott) has different morphology from common elephant grass (P. purpureum). It has several advantages compared to common elephant grass in term of faster growth and regrowth rates, high of leaf and stem ratio, protein content, and dry matter production. This grass is suitable for grazing and cut and carry system. This grass is also suitable for ruminant feed as silage or hay. Processing of dwarf elephant grass using fermentation technology is recommended during over production period, for further use during drought and limited forage availability.